Characterizing the Biology of Lytic Bacteriophage vB_EaeM_φEap-3 Infecting Multidrug-Resistant Enterobacter aerogenes - Zhao, Jiangtao; Zhang, Zheng; Tian, Changyu; Chen, Xiao; Hu, Lingfei; Wei, Xiao; Li, Huan; Lin, Weishi; Jiang, Aimin; Feng, Ruo; Yuan, Jing; Yin, Zhe; et al. (Frontiers in Microbiology, 2019)
Carbapenem-resistant Enterobacter aerogenes strains are a major clinical problem because of the lack of effective alternative antibiotics. However, viruses that lyse bacteria, called bacteriophages, have potential therapeutic applications in the control of antibiotic-resistant bacteria. In the present study, a lytic bacteriophage specific for E. aerogenes isolates, designated vB_EaeM_φEap-3, was characterized. Based on transmission electron microscopy analysis, phage vB_EaeM_φEap-3 was classified as a member of the family Myoviridae (order, Caudovirales). Host range determination revealed that vB_EaeM_φEap-3 lysed 18 of the 28 E. aerogenes strains tested, while a one-step growth curve showed a short latent period and a moderate burst size. The stability of vB_EaeM_φEap-3 at various temperatures and pH levels was also examined. Genomic sequencing and bioinformatics analysis revealed that vB_EaeM_φEap-3 has a 175,814-bp double-stranded DNA genome that does not contain any genes considered undesirable for the development of therapeutics (e.g., antibiotic resistance genes, toxin-encoding genes, integrase). The phage genome contained 278 putative protein-coding genes and one tRNA gene, tRNA-Met (AUG). Phylogenetic analysis based on large terminase subunit and major capsid protein sequences suggested that vB_EaeM_φEap-3 belongs to novel genus “Kp15 virus” within the T4-like virus subfamily. Based on host range, genomic, and physiological parameters, we propose that phage vB_EaeM_φEap-3 is a suitable candidate for phage therapy applications.